2020
DOI: 10.21638/spbu03.2020.105
|View full text |Cite
|
Sign up to set email alerts
|

Biological role and health benefits of antioxidant compounds in cereals

Abstract: Substances inhibiting or preventing oxidative damage in the target molecule are called antioxidants. It has been shown that antioxidants are substances that contribute to the prevention of a number of serious human diseases, and antioxidant activity is one of the important parameters for the quality of food products and ingredients. Phenolic compounds are of greatest importance for this review. It is now established that whole grain cereals contain a large number of bound polyphenols. It is known that cereals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 137 publications
0
15
0
1
Order By: Relevance
“…The AVEQ project (Avena genetic resources for quality in human consumption) analyzed 658 oat cultivars and confirmed the contribution of both genetic and environmental aspects to the formation of the tested character [49]. It is worth mentioning that, compared with cultivated and other wild di-and tetraploid oat species, higher contents of β-glucans and other antioxidants were found in the hexaploid (wild) A. fatua, A. occidentalis, and (cultivated) A. byzantina, and diploid (wild|) A. atlantica [38,39,[49][50][51].…”
Section: β-Glucansmentioning
confidence: 61%
See 4 more Smart Citations
“…The AVEQ project (Avena genetic resources for quality in human consumption) analyzed 658 oat cultivars and confirmed the contribution of both genetic and environmental aspects to the formation of the tested character [49]. It is worth mentioning that, compared with cultivated and other wild di-and tetraploid oat species, higher contents of β-glucans and other antioxidants were found in the hexaploid (wild) A. fatua, A. occidentalis, and (cultivated) A. byzantina, and diploid (wild|) A. atlantica [38,39,[49][50][51].…”
Section: β-Glucansmentioning
confidence: 61%
“…A study of naked and hulled oats showed that naked oat cultivars had significantly higher values of total antioxidant activity. Among hulled oat cultivars, these values were higher in dark-hulled forms compared with white-hulled oats [50].…”
Section: Phenolic Compounds and Avenanthramidesmentioning
confidence: 83%
See 3 more Smart Citations